Ultra-early Spinal Decompression Surgery Can Improve Neurological Outcome of Complete Cervical Spinal Cord Injury; a Systematic Review and Meta-analysis - Yousefifard, Mahmoud; Hashemi, Behrooz; Forouzanfar, Mohammad Mehdi; Khatamian Oskooi, Rozita; Madani Neishaboori, Arian; Jalili Khoshnoud, Reza (Archives of Academic Emergency Medicine, 2022)
Introduction: Early decompression within the first 24 hours after spinal cord injury (SCI) is proposed in current guidelines. However, the possible benefits of earlier decompression are unclear. Thus, the present meta-analysis aims to investigate the existing evidence regarding the efficacy of ultra-early decompression surgery (within 12 hours after SCI) in improving patients’ neurological status. Methods: A search was performed in Medline, Embase, Scopus and Web of Science electronic databases, until the end of August 2021. Cohort studies and clinical trials were included in the present study. Exclusion criteria were absence of an early or late surgery group, failure to report neurological status based on the American spinal injury association impairment scale (AIS) grade, failure to perform the surgery within the first 12 hours after SCI, and duplicate reports and review articles. Two independent reviewers performed data collection, and risk of bias and certainty of evidence assessments. The outcome was reported as odds ratio (OR) and 95% confidence interval (CI). Results: Data from 16 articles, which studied 868 patients, were included. Compared to early or late decompression surgery, ultra-early decompression surgery significantly improves patients’ neurological status (OR = 2.25; 95% CI: 1.41 to 3.58). However, ultra-early surgery in thoracolumbar injuries is not significantly more effective than early to late surgery. Moreover, ultra-early surgery in patients with a baseline AIS A increases the chance of neurologic resolvent up to 3.86 folds (OR=3.86; 95% CI: 1.50 to 9.91). Contrastingly, ultra-early surgery does not result in significant improvement compared to early to late surgery in patients with AIS B (OR = 1.32; 95% CI: 0.51 to 3.45), AIS C (OR = 1.83; 95% CI: 0.72 to 4.64), and AIS D (OR = 0.99; 95% CI: 0.31 to 3.17). Conclusion: Current guidelines emphasize that spinal decompression should be performed within 24 hours after SCI, regardless of injury severity and location. However, results of the present study demonstrated that certain considerations may be taken into account when performing decompression surgery: 1) in patients with AIS A injury, decompression surgery should be performed as soon as possible, since its efficacy in neurological improvement is 3.86 folds higher in the first 12 hours after injury. 2) ultra-early decompression surgery in patients with cervical injury is more effective than in patients with thoracic or lumbar injuries. 3) postponing decompression surgery to 24 hours in SCI patients with AIS B to D does not significantly affect the neurological outcome.